The internal concentration of organic substances in fish embryos—A toxicokinetic approach. (1st July 2013) - Kühnert, Agnes; Vogs, Carolina; Altenburger, Rolf; Küster, Eberhard
Abstract: In ecotoxicity assessment, the ambient exposure concentration is typically applied to quantify the toxic potential of xenobiotic substances. However, exposure and organism‐related differences in bioconcentration often cause a considerable variability of toxicity data. This can be minimized by using the internal organism concentration, because toxicokinetic modifying factors are considered implicitly. In the present study, the relationship between ambient and internal concentration–time profiles was investigated for zebrafish ( Danio rerio ) embryos. The aim was to gain a better understanding and interpretation of exposure‐based methods using this model organism. For this purpose, a simple and effective approach to determine the internal concentration was developed. Embryos were exposed to a series of 4 neutral organic substances (naphthalene, fluorene, fluoranthene, benz[ a ]anthracene) of different hydrophobicity for 72 h. The internal and ambient concentrations were measured at 8 to 9 time points. Kinetics of uptake and elimination were modeled using a first‐order 1‐compartment model. Biotransformation processes appeared to influence the internal concentrations of fluoranthene and benz[ a ]anthracene after 48 h. The bioconcentration factors (BCFs) obtained are in excellent agreement with those determined in previous studies using radiolabeled substances. The method demonstrated in the present study is a further step toward a refined ecotoxicity assessment using fish embryos, which links toxicity to the chemical concentration within the organism. This system may also be considered as an alternative to animal testing for BCF determination. Environ Toxicol Chem 2013;32:1819–1827. © 2013 SETAC